Dimensions of delusional experience scale: a psychometric evaluation of a German version - Büche, Liesa; Senger, Nana Christina; Kaiser, Stefan; Bock, Anique von; Grupe, Stefanie; Joest, Katharina; Barthel, Andreas; Vedder, Helmut; Mundt, Christoph; Kronmüller, Klaus-Thomas (Psychopathology, 2010)
Background: Delusional experience is a fundamental symptom of psychotic illness. Over recent years, a multidimensional perspective has become increasingly important regarding this phenomenon. Several instruments to measure different dimensions of delusions have been constructed. The aims of this study were to examine the reliability and validity of a German version of the Dimensions of Delusional Experience Scale (DDE). Methods: Two hundred inpatients with a schizophrenic spectrum disorder or an affective disorder with delusions were examined with the DDE, the Positive and Negative Syndrome Scale (PANSS) and other rating scales for delusional experiences. Results: The scale was found to have good reliability and excellent inter-rater reliability. The 2 factors, delusional involvement and delusional construct, found by Kendler et al. [Am J Psychiatry 1983;140:466-469] could be replicated. The convergent and differential validity of the scale was supported. Besides the content-related aspect ‘bizarreness’, the DDE mainly assesses cognitive aspects, emotional and behavioral aspects are not incorporated. Conclusions: The results support the value of a multidimensional perspective of delusional experiences. The German version of the DDE is a reliable and valid assessment tool for different dimensions of delusions, and an economical instrument for research and clinical practice. Further research is needed to reveal the dimensional structure underlying delusional experience.